Pembentukan dasar luar Amerika Syarikat - Suhana, Semawi (Universiti Malaysia Sarawak, UNIMAS, 2003)
The study on the American foreign policy decision making focused on the concept, goal, actors and factors that influence it. In discussing the goal of American foreign policy, this study will also considered the meaning of short, medium and long term goals.